Influence of the synergetic effect of the biocenosis synthesis of zoogenic colonies of bacteria and protozoa on the sustainable development of aquatic ecosystems - I. Tkacheva; D. Rudoy; A. Neidorf; A. Makoedov; V. Iarontovskii; Y. Kokhanov (Brazilian Journal of Biology)
Abstract The production of agricultural products, especially livestock and aquaculture products containing high amounts of protein, has a significant impact on the environment. However, humankind cannot forego the production of such products, since a balanced diet is necessary to maintain a healthy lifestyle. In Russia, where climatic features of most regions are unfavorable for agricultural activities, industrial aquaculture has a negative impact on the environment. In order to achieve the Sustainable Development Goals and develop a cyclic bioeconomy, it is necessary to improve fish keeping technologies in RAS or open ponds using probiotic-enriched Biofloc systems designed to purify water from biogenic nitrogen. When studying the synergistic effect of the interaction of various components of floc-forming systems, the most efficient formation of flocs by individual bacterial strains was revealed. The quality of floc protein allows using activated sludge with Bacillus probiotics to obtain floc biomass, which comprehensively reduces the costs of animal feeding, due to the processing of waste products into fodder raw materials. Also, improvement of the technology will reduce energy costs for water treatment, which will contribute to the achievement of sustainable development goals.